2019
DOI: 10.1101/678102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The expression of equine keratins K42 and K124 is restricted to the hoof epidermal lamellae ofEquus caballus

Abstract: HGH)2 29 Abstract 30 The equine hoof inner epithelium is folded into primary and secondary epidermal lamellae which 31 increase the dermo-epidermal junction surface area of the hoof and can be affected by laminitis, 32 a common disease of equids. Two keratin proteins (K), K42 and K124, are the most abundant 33 keratins in the hoof lamellar tissue of Equus caballus. We hypothesize that these keratins are 34 lamellar tissue-specific and could serve as differentiation-and disease-specific markers. Our 35 objectiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…While a number of keratin and actin filament proteins expressed in the lamellar tissue are also expressed in other epithelial tissues [63], it has recently been demonstrated that keratin protein, K124, is lamellar tissue-specific, highlighting the uniqueness of the lamellar epithelial tissue [64]. In addition to providing mechanical stability, the cytoskeleton also plays an important role intracellular signaling via mechanically-induced signal transduction [65].…”
Section: Lamellar Anatomy and Physiologymentioning
confidence: 99%
“…While a number of keratin and actin filament proteins expressed in the lamellar tissue are also expressed in other epithelial tissues [63], it has recently been demonstrated that keratin protein, K124, is lamellar tissue-specific, highlighting the uniqueness of the lamellar epithelial tissue [64]. In addition to providing mechanical stability, the cytoskeleton also plays an important role intracellular signaling via mechanically-induced signal transduction [65].…”
Section: Lamellar Anatomy and Physiologymentioning
confidence: 99%